أثر القرآن الكريم في الشّعر العربيّ -شعر البحتريّ أنموذجًا- (مجلة إحالات, 2025)
أبهر القرآن الكريم عقول النّاس وألبابهم وأَسَرَ قلوبهم واستولى على نفوسهم منذ نزوله على سيّد الأمّة محمّد صلّى الله عليه وسلّم، وذلك لما تميّز به عن سائر كلام البشر بجزالة الألفاظ وفصاحتها، وابتعاده عن الحوشي، وسحر بيانه وحسن وجودة سبكه. فقد تحدّى القرآن جميع الفصحاء، فوقفوا حِيَاله وقفة المبهوتين الضّعفاء الّذين لا حول ولا قوّة لهم معلنين ضعفهم وعجزهم. وقد استولى سحر ألفاظ القرآن على ألباب الأدباء والشّعراء خاصّة المعروفين بحسّهم المرهف وأذواقهم الرّاقية الرّفيعة. والبحتري (ت284ه) أحد الشّعراء المولعين بالاقتباس من القرآن الكريم، ويظهر ذلك جليّا في عدّة مواضع من ديوانه. فتجده تارة يقتبس لفظة أو أكثر في أبياته الشّعريّة، وتارة أخرى يضّمن آية كاملة، ويشير في مرّات أخرى إلى مجموعة من القصص القرآنيّ على نحو ما انتهجه سابقوه ممّن شاع الاقتباس من القرآن في أشعارهم.Abstract The Holy Qur'an has impressed the minds of people, their hearts, and captured their hearts and captured their souls since its descent upon The Lord of the Nation Muhammad, may God pray upon him and peace be upon him, because he distinguished him from all the words of mankind by the argument of words and their eloquence, his distance from al-Hashi, the charm of his statement and the goodness and quality of his sacrimi. The Qur'an defied all the Classical and they stood by the two weak and powerless people, declaring their weakness and helplessness. The magic of the words of the Qur'an has captured the hearts of writers and poets, especially those known for their refined sense and refined tastes. Al-Bahtri (T284Ah) is one of the poets who is fond of quoting the Qur'an, and this is evident in several places of his diwan. You find him sometimes quoting one or more words in his poetry verses, and at other times he includes a complete verse, and refers again to a series of Qur'anic stories, as his predecessors have suggested, and the quotation from the Qur'an in their poems is common.